2000
DOI: 10.1046/j.1444-2906.2000.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in gill chloride cells during smoltification in wild and hatchery-reared masu salmon Oncorhynchus masou

Abstract: SUMMARY: Ultrastructural changes in gill chloride cells during smoltification were examined in wild and hatchery‐reared masu salmon. On the filament, two types of chloride cells (α and β) and accessory cells were observed in wild fish from January (parr) to May (full‐smolt), while only α and accessory cells (α‐a cells) were observed in hatchery‐reared fish from March (pre‐smolt) to May (full‐smolt). Among α‐a cells of both types of fish, development of rough endoplasmic reticulum (ER) and Golgi apparatus was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Cortisol induces increase in transcript levels and synthesis of gill Na + ,K + -ATPase α-subunit in masu salmon (Ura et al, unpublished data). In masu salmon, development of the rough endoplasmic reticulum and Golgi apparatus were observed in gill chloride cells in March and April, suggesting active synthesis of new proteins including Na + ,K + -ATPase (Mizuno et al, 2000). These informations may suggest that cortisol acts directly in CR of the gill chloride cell, then it induces increase in synthesis of Na + ,K + -ATPase α-subunit in the gill chloride cell during increase in serum cortisol concentrations.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Cortisol induces increase in transcript levels and synthesis of gill Na + ,K + -ATPase α-subunit in masu salmon (Ura et al, unpublished data). In masu salmon, development of the rough endoplasmic reticulum and Golgi apparatus were observed in gill chloride cells in March and April, suggesting active synthesis of new proteins including Na + ,K + -ATPase (Mizuno et al, 2000). These informations may suggest that cortisol acts directly in CR of the gill chloride cell, then it induces increase in synthesis of Na + ,K + -ATPase α-subunit in the gill chloride cell during increase in serum cortisol concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…To enhance seawater adaptability in the gill, Na + ,K + -ATPase activity increases as do the size and number of chloride cells, which facilitate ion exchange between the internal and external environment (McCormick, 1995). The ultrastructure of the chloride cell also changes dramatically (Mizuno et al, 2000). It has been shown that these changes are mainly regulated by the action of cortisol and growth hormone (GH) (McCormick, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it may be speculated that increased smolt sensitivity results from morphological changes in the gill epithelium during smolting, including an increase in the number and size of chloride cells , as well as ultrastructural changes in chloride cell associations with other cells in the gill (Pisam et al, 1988;Mizuno et al, 2000). In particular, Pisam et al (1988) demonstrated that accessory cells linked to apical portions of chloride cells by shallow junctions were present in Atlantic salmon smolts but not in parr.…”
Section: Discussionmentioning
confidence: 99%
“…MRCs on filaments were much larger than those on lamellae that also have been found in anadromous salmonids (Mizuno et al 2000;Uchida et al 1996) and shad (Zydlewski and McMormick 2001). MRCs in both locations are often present in hyposmotic environments, whereas in hyperosmotic environments, lamellar MRCs are often not present, presumably because active ion uptake is not as necessary, although ion uptake can also occur from cells located on the filament as well (Laurent et al 2006).…”
Section: Discussionmentioning
confidence: 92%